2014
DOI: 10.1007/s12192-013-0471-6
|View full text |Cite
|
Sign up to set email alerts
|

The co-chaperone DNAJC12 binds to Hsc70 and is upregulated by endoplasmic reticulum stress

Abstract: Human DNAJC12 is a J domain-containing protein whose regulation, subcellular localization, and function are currently unknown. We show here that the abundance of DNAJC12 in human LNCaP prostate cancer cells is upregulated by the stress-inducing drug A23187 and by the stressregulated transcription factor AIbZIP/CREB3L4. The DNAJC12 gene encodes two isoforms, only one of which (isoform a) is expressed in these cells. Immunofluorescence studies showed that a recombinant DNAJC12 protein is diffusely distributed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Possible differences in the transcriptional regulation between wt and Enu 1/1 mice were determined by mRNA quantification (RT‐qPCR). We measured the mRNA levels of Dnajc12 and Pah , as well as those for other selected genes based on their possible interactions with DNAJC12, including (i) the molecular chaperones Hsp70 ( Hspa1b ), Hsc70 ( Hspa8 ), HSF1 ( Hsf1 ), and BIP ( Hspa5 ), the latter being an endoplasmatic reticulum chaperone that is associated with DNAJC12 in situations of cellular stress (Choi et al., ), and the co‐chaperone/E3 ubiquitin‐protein ligase CHIP ( Stub1 ); (ii) the eukaryotic translation elongation factor 1 delta EEF1D ( Eef1d ), which has been found to interact with DNAJC12 in a transcription factor interaction network (Miyamoto‐Sato et al., ); (iii) the estrogen receptors 1 and 2 ESR1 and 2 ( Esr1 , Esr2 ), and the G protein‐coupled estrogen receptor 1 ( Gper1 ), which were analyzed because DNAJC12 expression has been associated with estrogen receptor status in breast cancers (De Bessa et al., ); and (iv) GTP cyclohydrolase 1 ( Gch1 ) and GTP cyclohydrolase 1 feedback regulatory protein ( Gchfr ), which are involved in the synthesis of the PAH‐cofactor tetrahydrobiopterin (BH 4 ). The results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible differences in the transcriptional regulation between wt and Enu 1/1 mice were determined by mRNA quantification (RT‐qPCR). We measured the mRNA levels of Dnajc12 and Pah , as well as those for other selected genes based on their possible interactions with DNAJC12, including (i) the molecular chaperones Hsp70 ( Hspa1b ), Hsc70 ( Hspa8 ), HSF1 ( Hsf1 ), and BIP ( Hspa5 ), the latter being an endoplasmatic reticulum chaperone that is associated with DNAJC12 in situations of cellular stress (Choi et al., ), and the co‐chaperone/E3 ubiquitin‐protein ligase CHIP ( Stub1 ); (ii) the eukaryotic translation elongation factor 1 delta EEF1D ( Eef1d ), which has been found to interact with DNAJC12 in a transcription factor interaction network (Miyamoto‐Sato et al., ); (iii) the estrogen receptors 1 and 2 ESR1 and 2 ( Esr1 , Esr2 ), and the G protein‐coupled estrogen receptor 1 ( Gper1 ), which were analyzed because DNAJC12 expression has been associated with estrogen receptor status in breast cancers (De Bessa et al., ); and (iv) GTP cyclohydrolase 1 ( Gch1 ) and GTP cyclohydrolase 1 feedback regulatory protein ( Gchfr ), which are involved in the synthesis of the PAH‐cofactor tetrahydrobiopterin (BH 4 ). The results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Possible differences in the transcriptional regulation between wt and Enu 1/1 mice were determined by mRNA quantification (RT-qPCR). We measured the mRNA levels of Dnajc12 and Pah, as well as those for other selected genes based on their possible interactions with DNAJC12, including (i) the molecular chaperones Hsp70 (Hspa1b), Hsc70 (Hspa8), HSF1 (Hsf1), and BIP (Hspa5), the latter being an endoplasmatic reticulum chaperone that is associated with DNAJC12 in situations of cellular stress (Choi et al, 2014), and the Gper1 was faintly expressed, and Hsp70 also showed low expression.…”
Section: Quantification Of Gene Expression Of Pah Dnajc12 and Assocmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower CSF 5-HIAA compared to CSF HVA levels could be associated with a stronger interaction between DNAJC12 and tryptophan hydroxylase. DNAJC12 interacts with an additional 44 proteins, 21 of which are localized in the mitochondria, suggesting that DNAJC12 might have an important role in the mitochondrial process [8]. Pyruvate carboxylase, a key regulator of tricarboxylic acid cycle, was the most commonly identified mitochondrial protein interacting with DNAJC12 [8].…”
Section: Discussionmentioning
confidence: 99%
“…DNAJC12 interacts with an additional 44 proteins, 21 of which are localized in the mitochondria, suggesting that DNAJC12 might have an important role in the mitochondrial process [8]. Pyruvate carboxylase, a key regulator of tricarboxylic acid cycle, was the most commonly identified mitochondrial protein interacting with DNAJC12 [8]. A wider range of clinical and biochemical phenotypes may be associated with DNAJC12 variants in the future.…”
Section: Discussionmentioning
confidence: 99%